PENGHAYATAN COMMUNIO UMAT ALLAH MASA PANDEMIK COVID-19 - Pamungkas, Cornelius Septian Danny; Tukan, Antonius Ignasius Nggino (Pastoralia Jurnal Penelitian Dosen, 2021)
The focus of the study in this article is research on the impact of the Covid-19 pandemic in Jember Regency on the implementation of Catholic families. This study is reviewed philosophically from phenomenological thinking. This phenomenological research aims to understand the life experiences of someone who directly experiences an event. To determine this impact, this article uses qualitative research methodology. The research subjects interviewed were two people in the parish of St. Yusup, Jember, Malang Diocese.  This research found that the Covid-19 pandemic in Jember did not hinder the growth of the Catholic faith in the communio. These findings challenge the implementation of pastoral care  in the field of fellowship that is more strategic,  targeted and effective for the people in the Covid-19 pandemic situation in Jember Regency.